2019
DOI: 10.1088/1742-6596/1378/4/042033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of the performance characteristic of an eco-friendly HC600a as a retrofitting refrigerant in a thermal system

Abstract: The negative influence of refrigerants on the climate and the immediate environment in terms of their higher global warming potential (GWP) and ozone depletion potential (ODP) has prompted this study. Currently, natural refrigerants are the preferred alternative refrigerants and hydrocarbon is numbered among these natural refrigerants with zero ODP and negligible GWP. In order to improve and enhance the performance of the refrigeration system, the performance characteristics of the system were investigated exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The average values for these three refrigerants are 11.04 %, 6.99 % and 1.47 %, respectively less than that of R134a. Banjo et al [27] also reported 4.5 % reduction in energy consumption when R134a system was retrofitted with R600a.…”
Section: ____________________________________________________________________________ 2021 / 25mentioning
confidence: 93%
“…The average values for these three refrigerants are 11.04 %, 6.99 % and 1.47 %, respectively less than that of R134a. Banjo et al [27] also reported 4.5 % reduction in energy consumption when R134a system was retrofitted with R600a.…”
Section: ____________________________________________________________________________ 2021 / 25mentioning
confidence: 93%
“…The use of HCFCs will be limited to 2020 and 2030 in developed and underdeveloped countries. Likewise, Du Pont's chemical manufacturer declared that the HCFC substances' production should be ceased but would persist in making it available for existing equipment until their expiry period [39][40][41].…”
Section: Low-temperature Technologymentioning
confidence: 99%
“…The improvement in terms of efficiency of refrigeration systems has multiple approaches, from the retrofitting of the current refrigerant [3,4], to the replacement of the classical systems with hybrid systems [5][6][7]. However, in scenarios where the refrigeration machinery cannot be modified due to economical or process restrictions, the refrigeration systems are commonly improved by manipulating the generation part, composed by the compressors and the condensers, or modifying the temperatures of operation, the evaporation and condensation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%